2015
DOI: 10.1111/1462-2920.12837
|View full text |Cite
|
Sign up to set email alerts
|

Understanding fungal functional biodiversity during the mitigation of environmentally dispersed pentachlorophenol in cork oak forest soils

Abstract: Pentachlorophenol is globally dispersed and contamination of soil with this biocide adversely affects its functional biodiversity, particularly of fungi -key colonisers. Their functional role as a community is poorly understood, although a few pathways have been already elucidated in pure cultures. This constitutes here our main challenge -elucidate how fungi influence the pollutant mitigation processes in forest soils.Circumstantial evidence exists that cork oak forests in N.W. Tunisia -economically critical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 65 publications
(96 reference statements)
1
19
0
Order By: Relevance
“…Recently, we showed the existence of undefined active sources of PCP pollution in the Tabarka district (Tunisia), particularly in soils collected within cork oak forests [ 4 , 7 ]. The soils were contaminated with PCP levels ranging from 13 to 28 μg/kg of soil.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, we showed the existence of undefined active sources of PCP pollution in the Tabarka district (Tunisia), particularly in soils collected within cork oak forests [ 4 , 7 ]. The soils were contaminated with PCP levels ranging from 13 to 28 μg/kg of soil.…”
Section: Introductionmentioning
confidence: 99%
“…The soils were contaminated with PCP levels ranging from 13 to 28 μg/kg of soil. The source and history of the pollution in these soils is unknown [ 4 , 7 ]. Furthermore, we demonstrated that fungi isolated from these PCP-polluted forest soils can extensively degrade PCP, in theory acting as a buffer against PCP pollution in these habitats [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our front-runner candidates for study organisms were undoubtedly filamentous fungi. Fungi, which are unique and remarkable eukaryotic organisms, act as key colonizers of the soil and ensure major ecosystem functions, including the mitigation of hazardous chemicals ( Harms et al, 2011 ; Varela et al, 2015 ). Moreover, these organisms are well known as proficient producers of enzymes and metabolites of great biotechnological and pharmacological interest.…”
mentioning
confidence: 99%